2014
DOI: 10.1038/srep06039
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic oscillation and random-number generation based on nanoscale optical-energy transfer

Abstract: By using nanoscale energy-transfer dynamics and density matrix formalism, we demonstrate theoretically and numerically that chaotic oscillation and random-number generation occur in a nanoscale system. The physical system consists of a pair of quantum dots (QDs), with one QD smaller than the other, between which energy transfers via optical near-field interactions. When the system is pumped by continuous-wave radiation and incorporates a timing delay between two energy transfers within the system, it emits opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…To characterise the ‘chaotic probability’ observed in the nanoscale optical energy transfer between quantum dots (QDs)6, we investigated one-dimensional random walks with fluctuating biases generated by fixed, periodic, quasi-periodic, and chaotic time series. In this study, we demonstrated that the ETVAR clearly characterises the diffusive nature in random walks with fluctuating biases in the time-quenched framework, while the ETMSD does not estimate the diffusivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To characterise the ‘chaotic probability’ observed in the nanoscale optical energy transfer between quantum dots (QDs)6, we investigated one-dimensional random walks with fluctuating biases generated by fixed, periodic, quasi-periodic, and chaotic time series. In this study, we demonstrated that the ETVAR clearly characterises the diffusive nature in random walks with fluctuating biases in the time-quenched framework, while the ETMSD does not estimate the diffusivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mean of p(t ) is exactly 0.5, which implies that the net bias is zero. Figure 5 shows four different time series of p(t ) obtained from a data set of nanophotonic oscillations6: e.g. (a) fixed, (b) periodic (No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum dots [5,6], single photon avalanche photodiode (SPAD) [7], light emitting devices (LEDs) [8,9], laser [10,11], chaotic laser [12] , and atmospheric turbulence [13] have been employed as sources of entropy to produce random numbers. In this paper we present a quantum RNG (QRNG) based on silicon nanocrystals (SiNCs) LEDs, able to produce statistically good bit sequences using a simple experimental setup for data extraction.…”
Section: A Introductionmentioning
confidence: 99%